Biochemistry and molecular biology of plant hormones - Hooykaas, P.P.J (Elsevier, 2012)
This text provides up-to-date coverage of a variety of topics within the field of plant hormones. There is a particular emphasis on biosynthesis, metabolism and mechanisms of action. It should be useful to university libraries and scientists in the biotechnology sector